WHAT PREDICTS MORE THE SALES-FORCE PERFORMANCE: MOTIVATION OR SATISFACTION IN THE INSURANCE INDUSTRY? - Kumar Sahoo, Saroj; Mangaraj, Sovan; sahoo3Sandhyarani (British Journal of Marketing Studies, 2015)
The age old phenomenon-cum-debate that motivated employees can work more/better or satisfied employees can work more/better, is being solved to a little extent or more of assumptions are taken to solve or solved for less-stressed employees, but not for the stressed employees like sales-force in insurance industry. The current study aiming at solves this managerial problem by taking sample size of 270 (life insurance sales employees/agents in general). Here it is found that motivation-factors like fair treatment, work culture, participatory system, rationalization, work environment, individual recognition, and scope of development can produce sales force performance significantly, but not the satisfaction of life insurance sales-force in India. Satisfaction-factors show no relation with the sales-force performance. Factors extracted by explorative factor analysis put into the linear regression with the dependent variable as sales-force performance.